Mannose-binding lectin 2 (MBL2) gene polymorphisms do not influence frequency of infections in chronic lymphocytic leukemia patients - Holanda,Katarina (2014)
Background: Infectious complications represent the main cause of morbidity and mortality in chronic lymphocytic leukemia. It has been reported that polymorphisms of the mannosebinding lectin 2 (MBL2) genes are correlated with MBL protein serum levels and, consequently, are associated with the development of infectious diseases. Objective: The purpose of this study was to investigate the possible association between MBL2 gene polymorphisms and risk of infection in chronic lymphocytic leukemia patients. Methods: Peripheral blood samples from 116 chronic lymphocytic leukemia patients were collected; after genomic DNA extraction, real time polymerase chain reaction was used to determine the polymorphisms of the promoter region and exon 1 of the MBL2 gene. Results: A high frequency of Binet stage A (p-value = 0.005) and absence of splenomegaly (p-value = 0.002) were observed in patients with no infection; however, variant alleles/ genotypes and haplotypes of this gene had no impact on the risk of infection. Conclusion: To the authors' knowledge, this is the first study describing the association between MBL2 polymorphisms and infectious disease in chronic lymphocytic leukemia. Although it was not possible to demonstrate any influence of MBL2 polymorphisms as a genetic modulator of infection in chronic lymphocytic leukemia, the authors believe that the present data are clinically relevant and provide the basis for future studies.